Serotonin Receptor 5-HT3A Affects Development of Bladder Innervation and Urinary Bladder Function - Ritter, K. Elaine; Wang, Zunyi; Vezina, Chad M.; Bjorling, Dale E.; Southard-Smith, E. Michelle (Frontiers in Neuroscience, 2017)
The autonomic and sensory nervous systems are required for proper function of all visceral organs, including the lower urinary tract (LUT). Despite the wide prevalence of bladder dysfunction, effective treatment options remain limited. Pelvic innervation regenerative strategies are promising, but surprisingly little is known about the molecular factors driving the development of bladder innervation. Given prior evidence that serotonin receptor 5-HT3A is expressed early in LUT development and is an important mediator of adult bladder function, we sought to determine if 5-HT3A is required for the development of autonomic innervation of the bladder. We found that 5-HT3A is expressed early in fetal mouse pelvic ganglia and is maintained through adulthood. Htr3a knockout male mice, but not females, exhibit increased urinary voiding frequency compared to wild type littermates. Analysis of lower urinary tract function via anesthetized cystometry revealed decreased voiding efficiency in male Htr3a mutants. Htr3a-/- mutant animals exhibit a transient disturbance of autonomic neuronal subtype markers (tyrosine hydroxylase and choline acetyl transferase) within the fetal pelvic ganglia, although the imbalance of neuronal subtype markers assayed is no longer apparent in adulthood. Loss of 5-HT3A activity results in a higher density of autonomic and sensory neuronal fibers supplying bladder smooth muscle in both fetal and adult mice. Collectively, our findings highlight 5-HT3A as a critical component in the autonomic control of micturition and identify a novel role for this serotonin receptor in peripheral nervous system development.